The Epistles for All Christians : Epistolary Literature, Circulation, and The Gospels for All Christians - Smith, David, (Biblical Interpretation Series ;, 2021)
In The Epistles for All Christians, David Smith argues that epistolary literature offers analogous evidence of circulation to the Gospels. Since Richard Bauckham's edited volume The Gospels for All Christians was published in 1998, debate over the validity of the contributors' claims that the Gospels were written for "all Christians" has revolved around interpretation. Smith brings circulation to bear on the conversation. Studying ancient media practices of publication and circulation and using social network theory, Smith makes a compelling case that if the evangelists did not expect their texts to circulate they would be atypical.